Effect of feeding oats and oat hulls on performance of weanling pigs - A J Thulin; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1978)
Two hundred twenty-eight Yorkshire pigs, weaned at 5 weeks of age and averaging 8.4 kg. (18.46 lbs) were used to determine how feeding them various levels of oats, oat hulls, and oats plus fat would effect their performance. Adding oats or oat hulls to increase fiber content of the diets resulted in similar rates of gain, even though the diets contained up to 7.3% fiber. Pigs fed a diet containing 7.3% fiber, however had significantly poorer feed efficiency and daily feed intake than pigs fed the other diets tested. Pigs fed diets containing 10%, 20%, 30%, and 40% oats had slightly improved rates of gain and feed efficiency than pigs fed the control diet.; Swine Day, Manhattan, KS, November 9, 1978
Keywords: Swine day; 1978; Kansas Agricultural Experiment Station contribution; no. 79-105-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 342; Swine; Oats; Oat hulls; Performance; Weanling pigs; Rate of gain